Convergent recombination suppression suggests role of sexual selection in guppy sex chromosome formation - Alison E. Wright (Nature Portfolio, 2017)
It has been suggested that sex chromosomes arise as a result of sexual conflict, resulting in selection against recombination between chromosomes. Here, the authors resequence laboratory and wild guppy populations with differing levels of sexual antagonism, providing support for this long-held view.